Strategi Komunikasi Sosialisasi Program Generasi Berencana BBKBN Di Kota Gorontalo - Miftahul Jannah Adnan; Dwi Ratnasari; Ramansyah Ramansyah (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2021)
The program of Generasi Berencana (GenRe) or Generation Planning is a program designed to prepare and plan youthfor family life. In this program, the Office of the Population and Family Planning Agency promotes the maturity of themarriage age with the aim of increasing the media of the marriage age, especially for women. This study aims todiscover the communication strategy carried out by the Office of the Population and Family Planning Agency ofGorontalo Province in socializing the Generation Planning Program (GenRe) in Gorontalo City. This study uses adescriptive qualitative research method. The data collection is through observation and interviews. This study applies adata analysis technique with stages consisting of data collection, data reduction, data presentation, andverification/conclusion. The results of this study illustrate that the communication strategy carried out by the Office ofthe Population and Family Planning Agency of Gorontalo Province has been quite effective and efficient. However,there are still some obstacles that often occur during the socialization of the GenRe Program, namely in terms ofchoosing communication media, assessing the purpose of messages, and the role of communicators.